Nurses Education and Motivation Towards Nursing Documentation - Devi Mediarti; Rehana Rehana; Abunyamin Abunyamin (Jurnal Ners, 2018)
Introduction: Nursing documentation is an integral part that cannot be separated from healthcare as a responsibility and accountability of nurses. High education and motivation are needed to achieve good nursing documentation. The aim of this study was to know the correlation between education and motivation of nurses towards Intensive Care nursing documentation.Methods: The design used was an analytical survey with a cross-sectional approach. The population was nurses in intensive care of Palembang BARI Hospital with as many as 46 nurses and 44 samples obtained with total sampling. Data were collected by questionnaire and observational and were analyzed by Chi-Square. Independent variables are education and motivation of nurses and the dependent variable is nursing documentation.Results: There was a correlation between education (p=0.035) and motivation (p=0.040) of nurses towards nursing documentation.Conclusion: High education and motivation of nurses influenced towards the quality of nursing education. The nursing manager of the hospital is recommended affording the opportunity to support human resources in the hospital, especially for nurses to participate in education, in accordance with the demands of legislation in nursing education, and to organize the training of nursing documentation.